Simplify the expression by subtracting the radicals.

V50-28=6V

1 answer

To simplify the expression \( \sqrt{50} - 28 = 6\sqrt{?} \), we first need to simplify \( \sqrt{50} \).

We can break down \( \sqrt{50} \) as follows: \[ \sqrt{50} = \sqrt{25 \times 2} = \sqrt{25} \times \sqrt{2} = 5\sqrt{2} \]

Now we substitute this back into the equation: \[ 5\sqrt{2} - 28 = 6\sqrt{?} \]

Next, to isolate \( 6\sqrt{?} \), move \( 28 \) to the other side: \[ 5\sqrt{2} - 28 = 6\sqrt{?} \] So we can express \( 6\sqrt{?} \) as: \[ 6\sqrt{?} = 5\sqrt{2} - 28 \]

Now, divide both sides by \( 6 \): \[ \sqrt{?} = \frac{5\sqrt{2} - 28}{6} \]

We cannot readily simplify \( \frac{5\sqrt{2} - 28}{6} \) any further without additional context about the radical on the right side.

If you are solving for a specific value: \[ ? = \left(\frac{5\sqrt{2} - 28}{6}\right)^2 \]

Otherwise, this expression is simplified as far as it can go without further information or specific conditions on \( ? \). If you need more assistance or steps to solve for a specific number, please provide additional context!